2010
DOI: 10.17660/actahortic.2010.877.78
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Minimally Processed Cabbage in Different Packaging Systems

Abstract: A modificação nos hábitos alimentares da população brasileira em busca da melhoria na qualidade de vida e longevidade tem incentivado a procura por alimentos saudáveis, de excelente qualidade sensorial e garantia de sanidade, aumentando o consumo de hortaliças e frutas frescas (DURIGAN, 2004). O processamento mínimo objetiva suprir essas necessidades, disponibilizando produtos frescos, limpos, convenientes, preparados e adequados para o consumo em menor tempo (CANTWELL;SUSLOW, 2002). Consequentemente, ocorre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…In the banana inflorescence treated with calcium chloride the reduction in phenol content was less, which was because (means in the column followed by the same alphabet do not differ significantly by DMRT at 5%) (T 1 -Calcium (means in the column followed by the same alphabet do not differ significantly by DMRT at 5%)(T 1 -Calcium hypochlorite 100 ppm, T 2 -Calcium chloride 0.2%, T 3 -Citric acid 0.2%, T 4 -Calcium hypochlorite 100 ppm + Calcium chloride 0.2%, T 5 -Calcium hypochlorite 100 ppm + Citric acid 0.2%, T 6 -Calcium hypochlorite 100 ppm + Calcium chloride 0.2% + Citric acid 0.2%, T 7 -Calcium chloride 0.2% + Citric acid 0.2%, T 8 -Control) of the inhibitory action demonstrated by the chloride ions against polyphenol oxidase. The finding is similar to the prior reports of Rinaldi et al, (2010). Moline et al, (1999) in their study also reported that calcium chloride was able to reduce the enzymatic browning in minimally processed chinese cabbage.…”
Section: Resultssupporting
confidence: 91%
“…In the banana inflorescence treated with calcium chloride the reduction in phenol content was less, which was because (means in the column followed by the same alphabet do not differ significantly by DMRT at 5%) (T 1 -Calcium (means in the column followed by the same alphabet do not differ significantly by DMRT at 5%)(T 1 -Calcium hypochlorite 100 ppm, T 2 -Calcium chloride 0.2%, T 3 -Citric acid 0.2%, T 4 -Calcium hypochlorite 100 ppm + Calcium chloride 0.2%, T 5 -Calcium hypochlorite 100 ppm + Citric acid 0.2%, T 6 -Calcium hypochlorite 100 ppm + Calcium chloride 0.2% + Citric acid 0.2%, T 7 -Calcium chloride 0.2% + Citric acid 0.2%, T 8 -Control) of the inhibitory action demonstrated by the chloride ions against polyphenol oxidase. The finding is similar to the prior reports of Rinaldi et al, (2010). Moline et al, (1999) in their study also reported that calcium chloride was able to reduce the enzymatic browning in minimally processed chinese cabbage.…”
Section: Resultssupporting
confidence: 91%
“…In general, there was ascorbic acid content reduction in all treatments during storage. Ascorbic acid usually decreases during storage of minimally processed products (Rinaldi et al, 2009). Damage from cutting and enzyme interaction may lead to ascorbic acid loss (Klein, 1987).…”
Section: Ascorbic Acid and Cooking Timementioning
confidence: 99%
“…However; improper MA conditions may also adversely affect product quality. For most vegetables, modified atmospheres of between 2 and 5% O 2 and 3-8% CO 2 maximize product shelflife (O' Beirne, 1990;Day, 1991;Moleyar and Narasimham, 1994;Rinaldi et al, 2010). The optimum oxygen concentration for storage of shredded cabbage was considered to be between 5-7.5% according to Gorny (2001) or to 2.2 and 4.3% according to Kawano et al (1984).…”
Section: Introductionmentioning
confidence: 99%